Pemberdayaan UMKM Berbasis “One Village One Product (OVOP)” Sebagai Gerakan Ekonomi Kerakyatan Pada Industri Logam Desa Hadipolo Kudus - Rakhmawati, Ita (BISNIS, 2019)
One Village One Product (OVOP) is one of the programs initiated by the government in order to improve rural welfare and equality through empowering MSMEs. The purpose of this study was to see the effectiveness of the development of OVOP in the metal industry MSMEs in the Hadipolo, Jekulo Kudus. This research is a type of field research with a qualitative descriptive approach. The technique of collecting data through interviews, observation and documentation. The data analysis technique starts from reducing data to concluding. The parameters of OVOP-based empowerment analysis include objectives, initiators, parties involved, sources of funding, implementation stage, form of participation in determining products, designs, forms of assistance and marketing channels. The results of the study show that all of these parameters have been running but have not reached the maximum, efforts need to be made to improve.